NUCLEAR INCIDENT (MALFUNCTION, BOMBARDMENT OR TERROR) AROUND THE WORLD, LEVEL OF PREPAREDNESS AND CHALLENGING ACCEPTED REFERENCE SCENARIOS - LEVI, Ori Nissim (Studia Universitatis Babes-Bolyai Studia Europaea, 2019)
The rate of construction of nuclear reactors in the world that supply energy, the geopolitical situation such as with North Korea, Iran, and the rising tensions between the world powers raise the question of whether and when a large nuclear incident will occur. However, after examining several references scenarios for dealing with civil nuclear events and compering them to data obtained from interviews, a careful analysis of previous events, and investigating accidents, it is clear that the current models cannot deal properly with those events. The current plans for coping with nuclear accidents address only partial aspects of disaster management, do not offer accurate description of unfolding events, ignore newly obtain scientific data, and ignore the human factor in decision making level. The current paper will review why Reference Scenario to nuclear incidents accepted currently in various countries around the world are not up to date and shed light on the most critical aspect in proper nuclear disaster management - rational thinking pattern. The suggested model presented at this article, ONDM, is an innovative new mechanism and a more effective preparedness mechanism for nuclear disaster, as it takes under consideration past mistakes and provides tools for leaders to make informed decisions under conditions of uncertainty